Corn Response to Planting Date as Affected by Plant Population and Hybrid in Continuous Corn Cropping Systems. Issue 1 (20th March 2015) - Lindsey, A. J.; Thomison, P. R.; Mullen, R.; Geyer, A. B.
Abstract : Excessive rainfall in April and May often forces farmers in Ohio to plant or replant as much as half of their corn acreage as late as mid‐June. Short‐season hybrids that are earlier maturing than commonly grown maturities are planted after 1 June but optimum plant populations for these hybrids in late planting environments are not known. Field experiments were conducted at two Ohio locations (South Charleston and Custar in southwest and northwest OH respectively) in 2009 and 2010 to determine whether the economically optimum plant population in relation to corn grain yield is influenced by corn hybrid relative maturity and planting date. The experiments evaluated two planting dates (PD1‐ late April/early May and PD2‐ early/mid‐June), with subplots containing corn hybrids of differing maturities (102‐, 104‐, 111‐, and 113‐day relative maturity), and sub‐subplots comparing plant populations (20, 000; 25, 000; 30, 000; 35, 000; 40, 000; and 45, 000 plants A −1 ). Yields at the two locations, averaged across hybrids and plant populations, decreased 12 to 22% between PD1 and PD2. There were differences in yield response among hybrids for PD1 and PD2, but these differences were not strongly related to hybrid maturity. The economically optimum plant population was greater for PD1 than PD2 only at South Charleston. These results suggest in some Ohio environments, populations should be reduced regardless of relative maturity to optimize yield in June plantings in a continuous corn cropping system.